S109 Utility of the airway perturbation device in the diagnostic assessment of exertional wheeze and breathlessness. (December 2018) - Walsted, E; Fleming, L; Bush, A; Hull, JH
Abstract : Introduction: Exertional breathlessness and wheeze are common respiratory symptoms encountered in adolescents and young adults and often diagnosed as asthma despite limited objective supporting evidence. A key reason for this is the failure to accurately identify conditions that 'mimic' asthma, such as exercise induced laryngeal obstruction (EILO). This is highly prevalent yet currently requires highly specialist and invasive laryngoscopic techniques to establish a robust diagnosis. There is a need to establish rapid, non-invasive means for detecting EILO and the aim of this work was to evaluate the utility of a novel non-invasive hand-held device, the 'airflow perturbation device' (APD) in this clinical context. Methods: We recruited 30 participants (n=20 patients with exertional breathlessness and n=10 controls) in order to compare the APD response profiles, of inspiratory and expiratory resistance, measurements against the gold standard methodologies currently employed to diagnose either EILO (i.e. direct laryngoscopic visualization) or exercise induced bronchospasm (EIB) (i.e. serial spirometric measurement). In addition, we collected questionnaire data of breathlessness and upper airway function. Results: Of the 30 participants, 15 were found to have EILO and four were diagnosed with asthma. Patients with EILO were younger of a female predominance compared with those with asthma (table 1). There were no differences in APD response profiles between participants with EILO, asthma or healthy individuals (table 1), and a high level of between-subject variation in APD responses was observed in all groups. Likewise, EILO was not detected by either pre or post exercise spirometric evaluation. Participants with EILO had a higher symptom burden, as measured by the Dyspnea-12, Nijmegen and Pittsburgh VCD Index questionnaires, than participants with asthma and healthy individuals and had a lower self-assessed quality of life. Discussion: The APD device did not accurately detect EILO in our real-life cohort of referrals with unexplained exertional breathlessness. These findings conflict with previous studies, establishing the validity of this device and this discrepancy may be explained by patient cohort selection. Future work should focus on evaluating other non-invasive means of detecting EILO in the non-specialist setting. We are grateful to the British Lung Foundation for funding this research.